2004
DOI: 10.1108/97279810480000366
|View full text |Cite
|
Sign up to set email alerts
|

Customer satisfaction in the service sector: a case study of the airline industry

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Also, Oliver (1999) describes BL as a deep loyalty which causes customers to rebuy a product/service, which will always be preferred in the future, or become a customer again thus to buy the same brand or brand set in spite of the marketing efforts and situational effects, which have the potential to persuade customers to change their purchase habits. Future usage is related to customer satisfaction (Baisya and Sarkar, 2004), and customer satisfaction is also associated with BL. In other words, when a loyal consumer’s attitudes toward a family brand is highly activated, the loyal consumer is more likely to power through the clutter of brand alternatives even in a large consideration set, ultimately facilitating the process of affect transfer (He et al , 2016).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Also, Oliver (1999) describes BL as a deep loyalty which causes customers to rebuy a product/service, which will always be preferred in the future, or become a customer again thus to buy the same brand or brand set in spite of the marketing efforts and situational effects, which have the potential to persuade customers to change their purchase habits. Future usage is related to customer satisfaction (Baisya and Sarkar, 2004), and customer satisfaction is also associated with BL. In other words, when a loyal consumer’s attitudes toward a family brand is highly activated, the loyal consumer is more likely to power through the clutter of brand alternatives even in a large consideration set, ultimately facilitating the process of affect transfer (He et al , 2016).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Over the past few years a number of studies have been reported in literature, which have examined and compared quality management practices in different countries around the world and use suitable concept in some industries. Some of the widely cited case studies include Dalu et al (2000); Kannan et al (2002); Baisya et al (2004). All these studies belong to industrial sectors like automobile, electronics, textile industries etc.…”
Section: Review Of Literaturementioning
confidence: 99%
“…There exist findings that suggest that despite the focus of past studies on the relationship among customer satisfaction (CS) and behavioral intention (BI), the precise nature of the relationship between CS and customer relationship share (RS) is not clear particularly in the hotel industry (Lee et al, 2000;Oliver et al, 1997;Hooi Ting, 2004). Baisya and Sarkar (2004) poised the importance of satisfaction in predicting customers' future intentions in airlines industry. Singh (2015) also empirically tested that satisfaction is a key driver of future behavior in services sector.…”
Section: Introductionmentioning
confidence: 99%